Sadam Akhmad Music Performing Arts Management in Tegal City - Muhamad Habib Nurfajrin; Hafid Zuhdan Bahtiar (Edumaspul: Jurnal Pendidikan, 2024)
This study examines the performance management of indie musician Sadam Akhmad in Tegal City, focusing on his productivity in releasing musical works from 2018 to 2024. The aim of this research is to understand how performance management is applied by Sadam Akhmad to develop his music career, especially in the blues genre. The research method used is descriptive qualitative, with data collection techniques through observation, interviews, and content analysis. The results indicate that Sadam Akhmad implements management principles such as planning, organizing, execution, and evaluation in his performances. Supporting factors for the success of his performances include a solid management team, personnel flexibility, and the use of digital platforms for promotion. In conclusion, good management is key to maintaining performance quality and expanding Sadam Akhmad's audience in the indie music scene.